Review of the Method of Valuation of the SDR. (Policy Papers; Policy Paper, 2005)
This paper sets out the main issues for the 2005 review of the SDR currency basket and interest rate basket. It provides the basis for the quinquennial review by the Executive Board of the method of valuation of the SDR, in accordance with the Executive Board decision on the calculation of currency amounts for the SDR valuation basket adopted in the context of the 2000 review. The new valuation and interest rate baskets will come into effect on January 1, 2006, unless the Executive Board decides otherwise.